PENERAPAN MODEL PEMBELAJARAN PROGRESIF UNTUK MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR IPS - Suryanto dan Salamah (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2014)
Research aims to improve Creativity and Learning Achievement IPS through the Progressive Learning Model. This type of research is action research (Classroom Action Research). Subjects in this study were Grade 3 Tunjungseto SDN, Sempor, Kebumen Academic Year 2013/2014, amounting to 15 students. Research procedure includes four phases: planning, implementation, observation and reflection. Data collection methods used observation, questionnaires, and tests. Analysis of the data in this study using quantitative descriptive techniques. Research results show that 1) social studies Creativity can be enhanced through progressive learning. This is evidenced in the pre-cycle students' creativity percentage of 60.6%, an increase in the first cycle to the mean (68.5) and the second cycle of 86.5. 2) The results of social studies can be enhanced through progressive learning. This is evidenced in the pre cycle with an average value of 61.66%, in the first cycle increased to 72.33% and the second cycle increased to 85.00%. Progressive learning model can improve creativity and student achievement.